Coloured factory workers' perceptions regarding job evaluation - Atkins, Deborah (Organisational Psychology, 2023)
This research investigated coloured factory workers' perceptions regarding job evaluation. The research was done in an engineering manufacturing company in Epping, Cape Town. Fifty-six subjects were selected by means of a stratified random sample. Subjects were weekly paid factory workers in Peromnes grades 12 - 19, who had at least six months service with the company. Personal interviews of t three-quarters of an hour were carried out with each participant. The linked-pair comparison design developed by Bose (1956) for nine variables was used. This design required that each subject be shown nine pairs of jobs. In each case they had to indicate which job should be paid more and why. They were also asked their opinion of the current job evaluation system in use, namely the Peromnes system. Results were analysed on a group basis. It was found that there was a high correlation between the rankings as given by the workers and the Peromnes grading system. The most important criteria used by the factory workers in evaluating jobs were responsibility, contribution to production/profits, control/influence over quality and education and training. Results indicated that there were both similarities and differences in the criteria used by the workers and those used in most job evaluation systems. Workers generally regarded the Peromnes system as fair and equitable.